2015
DOI: 10.4103/1119-3077.154220
|View full text |Cite
|
Sign up to set email alerts
|

Important clinical and laboratory correlates of glomerular filtration rate in sickle cell anemia

Abstract: High serum direct bilirubin and ALP are associated with a deteriorating eGFR_MDRD. Other clinical and laboratory indicators of disease severity in SCD do not show the relationship with the GFR. MDRD_GFR estimation seemed to be a more appropriate method of estimating GFR in SCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
3
5
0
Order By: Relevance
“…This study examined the renal function of HbSS children in a steady state in a tertiary health facility. The mean eGFR of 146:5 ± 31:1 ml/min/1.73 m 2 in HbSS subjects is comparable to findings by Madu et al [17] (150 ± 74:8 ml/min/1.73 m 2 ) in Enugu South-East Nigeria, Abhulimhen-Iyoha et al [18] (148:96 ± 23:2 ml/min/1.73 m 2 ) in Benin City South-South Nigeria, and Bodas et al [4] (140 ml/min/1.73 m 2 ) in the USA. The mean eGFR in HbSS subjects in this study was significantly higher than that of age-and sex-matched HbAA subjects (128:7 ± 18:5 ml/min/1.73 m 2 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study examined the renal function of HbSS children in a steady state in a tertiary health facility. The mean eGFR of 146:5 ± 31:1 ml/min/1.73 m 2 in HbSS subjects is comparable to findings by Madu et al [17] (150 ± 74:8 ml/min/1.73 m 2 ) in Enugu South-East Nigeria, Abhulimhen-Iyoha et al [18] (148:96 ± 23:2 ml/min/1.73 m 2 ) in Benin City South-South Nigeria, and Bodas et al [4] (140 ml/min/1.73 m 2 ) in the USA. The mean eGFR in HbSS subjects in this study was significantly higher than that of age-and sex-matched HbAA subjects (128:7 ± 18:5 ml/min/1.73 m 2 ).…”
Section: Discussionsupporting
confidence: 88%
“…In this study, a weak positive correlation was found between eGFR and frequency of hospitalized past painful crisis. Similar to the index study, Bodas et al [4] and Madu et al [17] did not find any statistically significant correlation between eGFR and frequency of past painful crisis in their study. This may be due to few past history of painful crisis obtained from the subjects in this study.…”
Section: Discussionsupporting
confidence: 72%
“…The risk factors for leg ulceration are being a man, younger age (<20 years), low level of fetal hemoglobin, a hemoglobin level less than 6 g/dL, certain HLA types, and antithrombin deficiency. 8…”
Section: Clinical Presentationsmentioning
confidence: 99%
“…The risk factors for leg ulceration are being a man, younger age (<20 years), low level of fetal hemoglobin, a hemoglobin level less than 6 g/dL, certain HLA types, and antithrombin deficiency. 8 Recently vasculopathic abnormalities involving abnormal vascular tone and activated, adhesive endothelium have been recognized as a contributor to end organ damage in patients with SCD. 9 Vasculopathy of SCD has been implicated in the development of pulmonary hypertension, stroke, leg ulceration, and priapism linked to hemolytic severity.…”
Section: Clinical Presentationsmentioning
confidence: 99%
“…On the other hand, this study does not present any parameter related to kidney function, which provides the missing information of whether AST is related or not with SN 25 . However, Madu et al correlated AST levels and proteinuria, without statistical significance, which also indicates a poor correlation between this predictor and kidney injury 26 .…”
mentioning
confidence: 99%